Proportion of Dry Eye in Hepatitis C Patients - Aisha Azam, Samia Iqbal, Iftikhar Ahmed (Pakistan Journal of Ophthalmology, 2018)
Purpose: The main purpose of this study was to find out the proportion of dry eye in patients of hepatitis C. Study Design: Descriptive cross sectional study. Duration and Place of Study: Department of Ophthalmology, Alhaded Trust Hospital, Lahore. Duration of study January 2017 to august 2017. Material and Method: The study was conducted on 61 patients having positive history of hepatitis C with age range of 25-65 years. The sample size was collected by non-probability convenient method. All patients were diagnosed with Hepatitis C by Department of Medicine, Alhaded trust hospital after PCR. Patients of all other ages or having any other systemic disorders were excluded from the study. Schirmer test was used for the measurement of tear film breakup time. Data was collected by a self-designed proforma after written informed consent. Data entry and statistical analysis was done by Arithmetical Software SPSS. Results: Total 61 patients were included in the study. Out of 61 patients, 28 (45.9%) were females and 33 (54.1%) were males. There were 18 (29.5%) patients who were 25 to 35 years of age and 27 patients (44.3%) had age of 36 to 50 years. There were 16 patients (26.2%) who were 51 to 65 years of age. There were 17 (27.8%) patients who had normal tear breakup time, 14 (22.9%) had moderate tear breakup time and remaining 30 (49.1) had severely reduced tear breakup time. Conclusion: In patients of Hepatitis C, dry eye disorder is commonly present. Therefore, all patients with dry eyes should be evaluated for Hepatitis C. Key words: Dry eye disorder, hepatitis C.